The influence of sponsorship and social media marketing on brand awareness at the bites brownies - Januarty, Widalicin; Nainggolan, Elisabeth; Fenny, Fenny; Suci, Ratih Dwi (Junal Ilmu Manajemen, 2025)
Research conducted at Brownies The Bites aims to determine the variables that affect brand awareness of Brownies The Bites which is thought to be influenced by sponsorship and social media marketing. Research method used in this study was collecting data through literature review and field research, which was then analyzed systematically based on the study’s goals. In order to solve problems and prove the hypotheses, the data collected was then analyzed using descriptive analysis and regression analysis. The results of the research is Sponsorship partially has a positive and significant influence on Brand Awareness at The Bites Brownies. Social Media Marketing partially has a positive and significant influence on Brand Awareness at The Bites Brownies. Sponsorship and Social Media Marketing simultaneously have a positive and significant influence on Brand Awareness at The Bites Brownies. In this study, Brand Awareness is 68.7% influenced by sponsorship and social media marketing, while the remaining 31.3% is caused by various other factors that will not be explained in this study.